2017
DOI: 10.1093/humrep/dex013
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of hysterosalpingo-foam sonography in comparison to hysterosalpingo-contrast sonography with air/saline and to laparoscopy with dye

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 24 publications
1
47
0
2
Order By: Relevance
“…Normal pelvic organs were found in 161(73%) of the cases. Patient characteristics were similar to study observed by Ludwin et al 15 Similar or very close diseases incidences rate were also found with the same study done among 132 cases. SHSG was able to detect endometrial polyp in 2 cases.…”
Section: Discussionsupporting
confidence: 90%
“…Normal pelvic organs were found in 161(73%) of the cases. Patient characteristics were similar to study observed by Ludwin et al 15 Similar or very close diseases incidences rate were also found with the same study done among 132 cases. SHSG was able to detect endometrial polyp in 2 cases.…”
Section: Discussionsupporting
confidence: 90%
“…In CATnegative women, HSG was performed, and when tubal occlusion or abdominal pockets were seen on HSG, patients were referred for laparoscopy to confirm the presence of TFI. In women with patent tubes on HSG, no additional testing was done because of the high negative predictive value of HSG (Ludwin et al 2017). CAT-negative women who were considered at high risk for TFI due to endometriosis (based on history, physical examination and/or findings at ultrasound) were referred for laparoscopy immediately.…”
Section: Sample Collection and Definitionsmentioning
confidence: 99%
“…In fact, we believe that the bubbles were leaving the uterine cavity through the myometrial vessels and venous plexus, and reached the tubal and/or ovarian veins (Figure S3). Evaluation of tubal patency using foam (ExEM® Foam‐kit, hydroxyethylcellulose, glycerol and purified water; GynaecologIQ, Delft, The Netherlands) as contrast medium and power Doppler identified flow only in the right tube (Figure c) without signs of venous intravasation. There was no complication or pain following the examination and after a 2‐h observation period the patient left the clinic.…”
mentioning
confidence: 99%